Administrative Duties And Responsibilities of the Minister During Abbasside Era: For Period (247-334A.H.) (861-945A. D.) - YOUNIS, SAWSAN BAHJAT (Al-Adab Journal, 2020)
History of the ministry as we previously discussed , clarifies us , how had the ministers in more times power over caliphs , control on main positions and offices around Abbasside state , in addition to that become clear more numbers of ministers negatively affected on stability of matters and affairs in all over of the caliphate’s landsAlso we possibly concluded from texts were inherited that position of ministry was sold , bought , such as to pay moneys to obtain them , besides to interfere compromise or relatives or kinship relations without regard occasionally to efficiency and ability to manage matters . We can to say sometimes that princesses made to cancel or not to pay attention to role and powers of the minister . As an example for aforementioned which done by IBN RAEQ who was given position of leadership of the army , treasury and to supervise on councils and media . And even he commanded to address , to announce for him on all tribunes and forums . Where IBN ALATHEER stated : Whereas since that time ( 324 A.H. / 946 A.D. ) the divans were abolished and the minister did not check anything , but IBN RAEQ and his clerk review all cases .And in ( 334 A.H. – 946 A.D. ) the ministry was ended , officially dismissed and clerks do in stead of them , after Bauhinias occupied Baghdad and controlled over authorities .